Effect of die geometry on foaming behaviors of high melt strength polypropylene with CO2 - Lee P.C. (2014)
A systematic study is conducted to investigate the effect of die geometry (i.e., pressure and pressure-drop rate) on the cell-nucleation and growth behaviors of noncrosslinked high melt strength (HMS) polypropylene (PP) foams blown with supercritical CO2. The experimental results show that the cellular morphologies of PP foams are sensitive to the die geometry. The initial expansion behavior of the foam extrudate at the die exit is recorded using a high-speed CCD camera, which allows the study of die geometry effect on both initial expansion behavior and final cellular morphology. The effect of die temperature on the cell morphology is also studied.